2021
DOI: 10.1186/s12903-021-01648-3
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of dentin pretreatment on the resulting abrasive dentin wear

Abstract: Background This study aims to investigate the influence of different dentin pretreatment procedures on the resulting abrasive dentin wear. Methods Two groups (A, B) of 60 dentin samples each were prepared. Group A was brushed with an abrasive slurry (RDA = 85) and group B with a different abrasive slurry (RDA = 174). Four subgroups in each group (n = 15) were created (A1–A4) and (B1–B4). The subgroups were pretreated as follows: A1 + B1 with 1200-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…The dentin samples were pretreated with 2000‐ and 4000‐grit carborundum papers in this study, which has also been the case in other abrasion studies 17,18 . Regardless, a recent in vitro study reported that different pretreatment procedures of dentin samples do not seem to have an effect on the resulting abrasive dentin wear 12 . The applied brushing forces in this study (1–4 N) are also in accordance with most of other abrasion studies 19 .…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The dentin samples were pretreated with 2000‐ and 4000‐grit carborundum papers in this study, which has also been the case in other abrasion studies 17,18 . Regardless, a recent in vitro study reported that different pretreatment procedures of dentin samples do not seem to have an effect on the resulting abrasive dentin wear 12 . The applied brushing forces in this study (1–4 N) are also in accordance with most of other abrasion studies 19 .…”
Section: Discussionsupporting
confidence: 87%
“…As mentioned above, group C was brushed with almost twice stronger abrasive slurry as group A (RDA 133 vs RDA 71), which is also reflected in the mean abrasive values observed in both groups at 2‐, 3‐ and 4‐N brushing force. This agreement between RDA and profilometry methods was not always the case in previous studies 12,26 . Further elaborations might be necessary in this area.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…This might raise some questions on the relevance of the method vs consumer/patient use. The here used brushing time is kind of a standard and regularly used in testing abrasive dentin wear in vitro 23 , 25 , 26 . Furthermore, it's a worse-case scenario which might be reached under clinical conditions much later.…”
Section: Discussionmentioning
confidence: 99%